The Mixing Of Solid Waste From Palm Acid Oil (PAO) And Palm Kernel Cake (PKC) As A Source Of Animal Feed (Broiler) - Muhammad Amirul Syafiq, Nasarudin (2022)
Today, waste and waste management has given rise to many pressing issues. Waste management is a crucial area related to the economic status of a country and the lifestyle of its population. Wastewater pollution from high production of palm oil results in high production of palm oil mill effluent (POME) is a main problem throughout the world. This study is to focus on analysing the palm oil waste characteristics in manufacturing formulated chicken feed. Therefore, this study also focuses formulated chicken feed by using palm acid oil (PAO) and palm kernel cake (PKC). This study also to investigate the growth rate of chicken towards the formulation of chicken feed. In experiment, broiler chicken was used and divided into 2 groups of 15 chickens each with different formulation which are Diet 1 (D1), and Diet 2 (D2). Each diet contains different nutrient and composition. The chicken was fed with the formulation continuously for 42 days. The parameters to be analyse were body weight change (BWC). The result obtained from Diet 2 (D2) was recorded and compared with Diet 1 (D1) which are control diet (corn).